Labor Law Protection Due To Termination Of Employment Due To The Covid 19 Pandemic - Irawan Irawan; Ariman Sitompul; Melky Suhery Simamora (Legalpreneur Journal, 2022)
At the beginning of the Covid-19 pandemic, the implementation of policies regarding large- scale social restrictions had a very significant impact on companies in North Sumatra. Sources of data used in this study are primary and secondary data. The data analysis method used in this study is descriptive qualitative. Based on the results of the study, the conclusion in this study is the regulation of termination of employment due to the covid-19 pandemic which is regulated in Law Number 11 of 2020 concerning job creation, namely by reason of efficiency because the first in the provisions of Article 154 a paragraph of the job creation law states that "the company performs efficiency, either followed by the closure of the company or not followed by the closure of the company due to the company experiencing losses". The collective agreement is the result of a final agreement that should not be contested in the future from both the workers and employers. Termination of employment due to COVID-19 in Indonesia, the average layoff is not because the company is closed or closed, but because of the implementation of Work from Home which is a recommendation from the government.Â Â Â